Preparation method of high-sphericity-degree aluminum nitride heat-conducting filler

Through the combination of wet ball milling, spray granulation and nitride isolation powder, the agglomeration of aluminum nitride thermal filler during sintering is solved, the thermal conductivity and preparation efficiency are improved, the process is simplified and the cost is reduced.

CN119841646AActive Publication Date: 2025-04-18XIAMEN XINHUATE PORCELAIN NEW MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510177539.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2025-04-18
Estimated Expiration
2045-02-18

AI Technical Summary

Technical Problem

Existing aluminum nitride thermal fillers are prone to agglomeration during the sintering process, resulting in poor thermal conductivity and poor preparation efficiency and quality.

Method used

Ball-type aluminum nitride granulation powder is prepared by wet ball milling and spray granulation technology, and nitride isolation powder is added before high-temperature sintering to prevent agglomeration, and then modified with a thermally conductive modifier.

Benefits of technology

The spherical shape and thermal conductivity of aluminum nitride thermal filler are significantly improved, the preparation process is simplified, the production cost is reduced, and subsequent mechanical crushing and dispersion treatment is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841646A_ABST
    Figure CN119841646A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of heat-conducting fillers, provides a preparation method of a high-sphericity-degree aluminum nitride heat-conducting filler, and solves the problems that existing aluminum nitride heat-conducting fillers are easy to agglomerate, relatively poor in heat-conducting property and relatively poor in preparation efficiency and preparation quality. Comprising the following steps: 1) mixing aluminum nitride powder, PVB (Polyvinyl Butyral) and absolute ethyl alcohol, carrying out wet ball milling, and then carrying out spray granulation to obtain spherical aluminum nitride granulated powder; 2) degreasing treatment; (3) mixing by a dry method to obtain precursor mixed powder; 4) sintering at high temperature; and 5) preparing a heat-conducting modifier, and carrying out modification reaction to obtain the high-sphericity-degree aluminum nitride heat-conducting filler.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heat-conducting filler preparation, and in particular to a method for preparing a heat-conducting aluminum nitride filler with high sphericity. Background Art

[0002] Aluminum nitride ceramics have the characteristics of high thermal conductivity, high electrical insulation, high temperature resistance and expansion coefficient matching that of silicon, and are an ideal electronic packaging material. With the increase in the density of electronic components and the widespread application of high-power integrated circuits, higher requirements are placed on the temperature rise and heat dissipation performance of electronic products. Among them, spherical aluminum nitride ceramics have comprehensive characteristics such as high thermal conductivity, high dielectric properties, high filling rate, and environmental protection and non-toxicity, and are widely used as thermal conductive fillers in thermal interface materials.

[0003] At present, the main conventional preparation method of aluminum nitride thermal conductive filler is to first obtain spherical granulated powder by granulating aluminum nitride powder, and then sinter the degreased granulated powder at high temperature to prepare aluminum nitride ceramic balls. However, since the high-temperature sintering process of granulated powder is a physical and chemical reaction process of densification into porcelain, a large amount of atomic diffusion rearrangement occurs in the direct contact part between the granulated powders, resulting in the sintered powder presenting a block-shaped sintered body connected to each other, which needs to be processed by mechanical crushing and dispersion. The crushing and dispersion process will cause the ceramic body to be damaged to a certain extent, reducing the sphericity, filling rate and thermal conductivity of the thermal conductive filler. In addition, the equipment and process required for crushing and dispersion are relatively cumbersome, which increases the production cost of the thermal conductive filler.

[0004] Chinese patent application No. 202311836763.5 discloses a method for preparing densified spherical aluminum nitride, which adopts the method of adding materials such as graphite and carbon black as isolation agents. Although it can prevent the connection phenomenon during the sintering process of aluminum nitride, it is required to perform a decarbonization step in the range of 500 to 800°C, which increases the energy consumption and process cost of the preparation. In addition, the decarbonization process is in an air or oxygen atmosphere, and there is a risk of oxidation on the surface of the aluminum nitride particles, which may lead to a decrease in the thermal conductivity of aluminum nitride.

[0005] In view of the above problems, the present invention provides a method for preparing spherical aluminum nitride thermally conductive filler from the perspective of improving the sphericity of aluminum nitride thermally conductive filler and the cost of the preparation process, which can effectively simplify the preparation process of spherical aluminum nitride filler and greatly improve the preparation efficiency and preparation quality of spherical aluminum nitride filler. Summary of the invention

[0006] Therefore, in view of the above problems, the present invention provides a method for preparing a high-sphericity aluminum nitride thermal conductive filler to solve the problems that the existing aluminum nitride thermal conductive fillers are prone to agglomeration, have relatively poor thermal conductivity, and have relatively poor preparation efficiency and preparation quality.

[0007] To achieve the above object, the present invention adopts the following technical solutions:

[0008] A method for preparing a high-sphericity aluminum nitride thermal conductive filler comprises the following steps:

[0009] S1, mixing 100-120 parts by weight of aluminum nitride powder, 5-10 parts by weight of PVB and 100-200 parts by weight of anhydrous ethanol, performing wet ball milling, and then performing spray granulation to obtain spherical aluminum nitride granulated powder;

[0010] S2, degreasing the spherical aluminum nitride granulated powder prepared in step S1 to obtain degreased aluminum nitride granulated powder;

[0011] S3, dry-mixing the degreased aluminum nitride granulated powder obtained in step S2 with the nitride isolation powder to obtain a precursor mixed powder;

[0012] S4, sintering the precursor mixed powder obtained in step S3 at high temperature to obtain a crude high-sphericity aluminum nitride thermal conductive filler;

[0013] S5, mixing anhydrous ethanol and a thermal conductivity modifier evenly, stirring for 30-60 minutes, then adding the crude high-sphericity aluminum nitride thermal conductive filler prepared in step S4, and continuing to stir for 3-4 hours to carry out a modification reaction. After the reaction is completed, a first mixed solution is obtained, and the first mixed solution is washed 3-5 times with anhydrous ethanol, filtered, and dried for 16-24 hours to obtain the high-sphericity aluminum nitride thermal conductive filler;

[0014] Wherein, the nitride isolation powder is: a mixture of one or two of boron nitride powder and high temperature calcined aluminum nitride powder in any proportion;

[0015] The preparation process of the thermal conductivity modifier is as follows:

[0016] Under the protection of N2, sodium hydride and tetrahydrofuran are mixed in a mass ratio of 1:3-5, stirred evenly, the temperature is raised to 180-200°C, a mixed solution of castor oil and tetrahydrofuran is added dropwise, and the reaction is carried out for 2-4 hours. After the reaction is completed, the mixture is cooled to room temperature, centrifuged, the supernatant is taken, and then the supernatant is distilled to evaporate excess tetrahydrofuran to obtain the thermal conductivity modifier.

[0017] Furthermore, in the mixed solution of castor oil and tetrahydrofuran, the mass ratio of castor oil to tetrahydrofuran is 1:1-3.

[0018] Furthermore, the wet ball milling time is 4-8h.

[0019] Furthermore, the spray granulation is carried out in a spray dryer with a feed rate of 2000-2500 mL / h, a spray pressure of 0.5-1 MPa, a hot air inlet temperature of 140-200°C, and an air outlet temperature of 80-100°C.

[0020] Furthermore, the particle size of the spherical aluminum nitride granulated powder in step S1 is 10 to 200 microns.

[0021] Furthermore, the degreasing treatment is carried out in air at a temperature of 450-600° C. for 12-16 hours, and the carbon content of the aluminum nitride granulated powder after degreasing is less than 500 ppm.

[0022] Furthermore, the particle size of the nitride isolation powder is 0.5 to 10 microns, and the added amount is 1 to 10 wt % of the weight of the degreased aluminum nitride granulated powder.

[0023] Furthermore, the high temperature sintering in step S4 is carried out in a nitrogen atmosphere, with a heating rate of 5°C / min, a sintering temperature of 1700-1900°C, and a holding time of 5-6h.

[0024] Furthermore, the calcination temperature of the high-temperature calcined aluminum nitride powder is higher than the high-temperature sintering temperature.

[0025] By adopting the above technical solution, the beneficial effects of the present invention are:

[0026] 1. The thermal conductivity modifier prepared by using sodium hydride and castor oil as raw materials has a long-chain fatty acid ester structure, which is conducive to the adsorption of the thermal conductivity modifier on the surface of aluminum nitride, thereby achieving effective modification of crude high-sphericity aluminum nitride thermal conductive filler, which can reduce the surface energy of aluminum nitride filler and avoid agglomeration between fillers; at the same time, it can improve the dispersibility of the filler, which is more conducive to the formation of a thermal conductive network, thereby improving the thermal conductivity.

[0027] 2. By adding nitride isolation powder to the degreased aluminum nitride granulated powder, direct contact between the granulated powders can be effectively avoided, and the powders after sintering can be prevented from presenting mutually connected block-shaped sintered bodies, thereby eliminating the need for subsequent mechanical crushing and dispersion processing steps. High-sphericity aluminum nitride thermal conductive fillers can be directly prepared after sintering.

[0028] 3. Boron nitride is used as isolation powder to mix with aluminum nitride granulated powder. The melting point of boron nitride is 2700℃, which is much higher than the sintering temperature of aluminum nitride thermal conductive filler. It can avoid melting reaction with aluminum nitride powder at sintering temperature, thereby effectively isolating the aluminum nitride granulated powder. The aluminum nitride thermal conductive filler with added boron nitride isolation powder is in a loose state after sintering and does not need to be crushed and dispersed.

[0029] 4. Aluminum nitride powder calcined at high temperature is used as isolation powder to be mixed with aluminum nitride granulated powder. After high-temperature calcination, the activity of aluminum nitride powder is greatly reduced, and its calcination temperature is higher than the sintering temperature of aluminum nitride thermal conductive filler, thereby avoiding melting reaction with aluminum nitride powder at sintering temperature, and effectively isolating aluminum nitride granulated powder. The aluminum nitride thermal conductive filler to which calcined aluminum nitride micron powder is added as isolation powder is in a loose state after sintering, and no crushing and dispersion treatment is required. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Schematic diagram of the synthesis reaction of the thermal conductivity modifier in Examples 1 to 3 of the present invention;

[0031] Figure 2 This is a test diagram of the high sphericity aluminum nitride thermal conductive filler in Example 1 of the present invention;

[0032] Figure 3 This is a test diagram of the high sphericity aluminum nitride thermal conductive filler in Example 2 of the present invention. DETAILED DESCRIPTION

[0033] Example 1

[0034] A method for preparing a high-sphericity aluminum nitride thermal conductive filler comprises the following steps:

[0035] S1. 100 parts by weight of aluminum nitride powder, 5 parts by weight of PVB and 100 parts by weight of anhydrous ethanol were mixed and wet-milled for 4 hours, and then spray-granulated. The spray-granulation was carried out in a spray dryer with a feed rate of 2000 mL / h, a spray pressure of 0.5 MPa, a hot air inlet temperature of 200° C., and an air outlet temperature of 80° C. to obtain spherical aluminum nitride granulated powder, the particle size of which was 10 μm.

[0036] S2, degreasing the spherical aluminum nitride granulated powder prepared in step S1, wherein the degreasing treatment is carried out in air at a temperature of 580° C. for 16 hours, and the carbon content of the aluminum nitride granulated powder after degreasing is 300 ppm, thereby obtaining the aluminum nitride granulated powder after degreasing;

[0037] S3, dry-mixing the degreased aluminum nitride granulated powder obtained in step S2 with the nitride isolation powder to obtain a precursor mixed powder;

[0038] S4, sintering the precursor mixed powder prepared in step S3 at high temperature, wherein the high temperature sintering is performed in a nitrogen atmosphere, with a heating rate of 5°C / min, a sintering temperature of 1700°C, and a holding time of 5h to obtain a crude high-sphericity aluminum nitride thermal conductive filler;

[0039] S5, mixing anhydrous ethanol and a thermal conductivity modifier evenly, stirring for 30 minutes, then adding the crude high-sphericity aluminum nitride thermal conductive filler prepared in step S4, and continuing to stir for 3 hours to carry out a modification reaction. After the reaction is completed, a first mixed solution is obtained, and the first mixed solution is washed three times with anhydrous ethanol, filtered, and dried for 16 hours to obtain the high-sphericity aluminum nitride thermal conductive filler;

[0040] The nitride isolation powder is boron nitride powder, the particle size of the nitride isolation powder is 3 microns, and the addition amount is 3wt% of the weight of the degreased aluminum nitride granulated powder. The boron nitride powder and the degreased aluminum nitride granulated powder are mixed by a V-type stirring mixer for 4 hours.

[0041] refer to Figure 1 , the preparation process of the thermal conductivity modifier is:

[0042] Under the protection of N2, sodium hydride and tetrahydrofuran are mixed in a ratio of 1:3 by mass, stirred evenly, the temperature is raised to 180°C, and a mixed solution of castor oil and tetrahydrofuran is added dropwise, wherein the mass ratio of castor oil and tetrahydrofuran is 1:1, and the reaction is carried out for 2 hours. After the reaction is completed, the mixture is cooled to room temperature, centrifuged, the supernatant is taken, and then the supernatant is distilled to evaporate excess tetrahydrofuran to obtain the thermal conductivity modifier.

[0043] refer to Figure 2 The high sphericity aluminum nitride thermal conductive filler prepared in this embodiment was tested and found to have good sphericity and was in a loose state after sintering, and did not require crushing and dispersion processes.

[0044] Example 2

[0045] A method for preparing a high-sphericity aluminum nitride thermal conductive filler comprises the following steps:

[0046] S1. 110 parts by weight of aluminum nitride powder, 6 parts by weight of PVB and 165 parts by weight of anhydrous ethanol were mixed and wet-milled for 6 hours, and then spray-granulated. The spray-granulation was carried out in a spray dryer with a feed rate of 2200 mL / h, a spray pressure of 0.8 MPa, a hot air inlet temperature of 200° C., and an air outlet temperature of 90° C. to obtain spherical aluminum nitride granulated powder, the particle size of which was 50 μm.

[0047] S2, degreasing the spherical aluminum nitride granulated powder prepared in step S1, wherein the degreasing treatment is carried out in air at a temperature of 550° C. for 12 hours, and the carbon content of the aluminum nitride granulated powder after degreasing is 300 ppm, thereby obtaining the aluminum nitride granulated powder after degreasing;

[0048] S3, dry-mixing the degreased aluminum nitride granulated powder obtained in step S2 with the nitride isolation powder to obtain a precursor mixed powder;

[0049] S4, sintering the precursor mixed powder prepared in step S3 at high temperature, wherein the high temperature sintering is performed in a nitrogen atmosphere, with a heating rate of 5°C / min, a sintering temperature of 1750°C, and a holding time of 5.5h to obtain a crude high-sphericity aluminum nitride thermal conductive filler;

[0050] S5, mixing anhydrous ethanol and a thermal conductivity modifier evenly, stirring for 45 minutes, then adding the crude high-sphericity aluminum nitride thermal conductive filler prepared in step S4, and continuing stirring for 3.5 hours to carry out a modification reaction. After the reaction is completed, a first mixed solution is obtained, and the first mixed solution is washed 4 times with anhydrous ethanol, filtered, and dried for 20 to obtain the high-sphericity aluminum nitride thermal conductive filler;

[0051] The nitride isolation powder is high-temperature calcined aluminum nitride powder, and the calcination temperature of the high-temperature calcined aluminum nitride powder is 1900°C; the particle size of the nitride isolation powder is 5 microns, and the addition amount is 5wt% of the weight of the degreased aluminum nitride granulated powder; a V-shaped stirring mixer is used to mix the high-temperature calcined aluminum nitride powder and the degreased aluminum nitride granulated powder, and the mixing time is 4h;

[0052] refer to Figure 1 , the preparation process of the thermal conductivity modifier is:

[0053] Under the protection of N2, sodium hydride and tetrahydrofuran are mixed in a ratio of 1:4 by mass, stirred evenly, the temperature is raised to 190°C, and a mixed solution of castor oil and tetrahydrofuran is added dropwise, wherein the mass ratio of castor oil and tetrahydrofuran is 1:2, and the reaction is carried out for 3 hours. After the reaction is completed, the mixture is cooled to room temperature, centrifuged, the supernatant is taken, and then the supernatant is distilled to evaporate excess tetrahydrofuran to obtain the thermal conductivity modifier.

[0054] refer to Figure 3 The high sphericity aluminum nitride thermal conductive filler prepared in this embodiment was tested and found to have good sphericity and was in a loose state after sintering, and did not require crushing and dispersion processes.

[0055] Example 3

[0056] A method for preparing a high-sphericity aluminum nitride thermal conductive filler comprises the following steps:

[0057] S1. 120 parts by weight of aluminum nitride powder, 10 parts by weight of PVB and 180 parts by weight of anhydrous ethanol were mixed and wet-milled for 8 hours, and then spray-granulated. The spray-granulation was carried out in a spray dryer with a feed rate of 2500 mL / h, a spray pressure of 1 MPa, a hot air inlet temperature of 200° C., and an air outlet temperature of 100° C. to obtain spherical aluminum nitride granulated powder, the particle size of which was 200 μm.

[0058] S2, degreasing the spherical aluminum nitride granulated powder prepared in step S1, wherein the degreasing treatment is carried out in air at a temperature of 600° C. for 12 hours, and the carbon content of the aluminum nitride granulated powder after degreasing is 300 ppm, thereby obtaining the aluminum nitride granulated powder after degreasing;

[0059] S3, dry-mixing the degreased aluminum nitride granulated powder obtained in step S2 with the nitride isolation powder to obtain a precursor mixed powder;

[0060] S4, sintering the precursor mixed powder obtained in step S3 at high temperature, wherein the high temperature sintering is performed in a nitrogen atmosphere, with a heating rate of 5°C / min, a sintering temperature of 1850°C, and a holding time of 6h to obtain a crude high-sphericity aluminum nitride thermal conductive filler;

[0061] S5, mixing anhydrous ethanol and a thermal conductivity modifier evenly, stirring for 60 minutes, then adding the crude high-sphericity aluminum nitride thermal conductive filler prepared in step S4, and continuing to stir for 4 hours to carry out a modification reaction. After the reaction is completed, a first mixed solution is obtained, and the first mixed solution is washed 5 times with anhydrous ethanol, filtered, and dried for 24 hours to obtain the high-sphericity aluminum nitride thermal conductive filler;

[0062] The nitride isolation powder is a mixture of boron nitride powder and high-temperature calcined aluminum nitride powder in equal proportions, wherein the calcination temperature of the high-temperature calcined aluminum nitride powder is 1900°C; the particle size of the nitride isolation powder is 2 microns, and the addition amount is 10wt% of the weight of the degreased aluminum nitride granulated powder; a V-type stirring mixer is used to mix the nitride isolation powder and the degreased aluminum nitride granulated powder for 4 hours;

[0063] refer to Figure 1 , the preparation process of the thermal conductivity modifier is:

[0064] Under N2 protection, sodium hydride and tetrahydrofuran are mixed in a ratio of 1:5 by mass, stirred evenly, the temperature is raised to 200°C, and a mixed solution of castor oil and tetrahydrofuran is added dropwise, wherein the mass ratio of castor oil and tetrahydrofuran is 1:3, and the reaction is carried out for 4 hours. After the reaction is completed, the mixture is cooled to room temperature, centrifuged, the supernatant is taken, and then the supernatant is distilled to evaporate excess tetrahydrofuran to obtain the thermal conductivity modifier.

[0065] Although the present invention has been specifically shown and described in conjunction with the preferred embodiments, it should be understood by those skilled in the art that various changes may be made to the present invention in form and details without departing from the spirit and scope of the present invention as defined by the appended claims, all of which are within the scope of protection of the present invention.

Claims

1. A method for preparing a high-sphericity aluminum nitride thermally conductive filler, characterized in that: The following steps are involved: S1, mixing 100-120 parts by weight of aluminum nitride powder, 5-10 parts by weight of PVB and 100-200 parts by weight of anhydrous ethanol, performing wet ball milling, and then performing spray granulation to obtain spherical aluminum nitride granulated powder; S2, degreasing the spherical aluminum nitride granulated powder prepared in step S1 to obtain degreased aluminum nitride granulated powder; S3, dry-mixing the degreased aluminum nitride granulated powder obtained in step S2 with the nitride isolation powder to obtain a precursor mixed powder; S4, sintering the precursor mixed powder obtained in step S3 at high temperature to obtain a crude high-sphericity aluminum nitride thermal conductive filler; S5, mixing anhydrous ethanol and a thermal conductivity modifier evenly, stirring for 30-60 minutes, then adding the crude high-sphericity aluminum nitride thermal conductive filler prepared in step S4, and continuing to stir for 3-4 hours to carry out a modification reaction. After the reaction is completed, a first mixed solution is obtained, and the first mixed solution is washed 3-5 times with anhydrous ethanol, filtered, and dried for 16-24 hours to obtain the high-sphericity aluminum nitride thermal conductive filler; Wherein, the nitride isolation powder is: a mixture of one or two of boron nitride powder and high temperature calcined aluminum nitride powder in any proportion; The preparation process of the thermal conductivity modifier is as follows: Under the protection of N2, sodium hydride and tetrahydrofuran are mixed in a mass ratio of 1:3-5, stirred evenly, the temperature is raised to 180-200°C, a mixed solution of castor oil and tetrahydrofuran is added dropwise, and the reaction is carried out for 2-4 hours. After the reaction is completed, the mixture is cooled to room temperature, centrifuged, the supernatant is taken, and then the supernatant is distilled to evaporate excess tetrahydrofuran to obtain the thermal conductivity modifier.

2. The method for preparing a high sphericity aluminum nitride thermal conductive filler according to claim 1, characterized in that: In the mixed solution of castor oil and tetrahydrofuran, the mass ratio of castor oil to tetrahydrofuran is 1:1-3.

3. The method for preparing a high-sphericity aluminum nitride thermal conductive filler according to claim 1, characterized in that: The wet ball milling time is 4-8h.

4. The method for preparing a high sphericity aluminum nitride thermal conductive filler according to claim 1, characterized in that: The spray granulation is carried out in a spray dryer, with a feed rate of 2000-2500 mL / h, a spray pressure of 0.5-1 MPa, a hot air inlet temperature of 140-200° C., and an air outlet temperature of 80-100° C.

5. The method for preparing a high sphericity aluminum nitride thermal conductive filler according to claim 1, characterized in that: The particle size of the spherical aluminum nitride granulated powder in step S1 is 10 to 200 microns.

6. The method for preparing a high-sphericity aluminum nitride thermal conductive filler according to claim 1, characterized in that: The degreasing treatment is carried out in air at a temperature of 450-600° C. for 12-16 hours, and the carbon content of the aluminum nitride granulated powder after degreasing is less than 500 ppm.

7. The method for preparing a high-sphericity aluminum nitride thermal conductive filler according to claim 1, characterized in that: The particle size of the nitride isolation powder is 0.5 to 10 microns, and the added amount is 1 to 10 wt % of the weight of the degreased aluminum nitride granulated powder.

8. The method for preparing a high-sphericity aluminum nitride thermal conductive filler according to claim 1, characterized in that: The high-temperature sintering in step S4 is carried out in a nitrogen atmosphere, with a heating rate of 5°C / min, a sintering temperature of 1700-1900°C, and a holding time of 5-6h.

9. The method for preparing a high-sphericity aluminum nitride thermal conductive filler according to claim 1, characterized in that: The calcination temperature of the high-temperature calcined aluminum nitride powder is higher than the high-temperature sintering temperature.

Citation Information

Patent Citations

  • Densified spherical aluminum nitride as well as preparation method and application thereof

    CN118185344A

  • Preparation method and application of aluminum nitride porous structural body

    CN113248262A

  • Preparation method of spherical aluminum nitride granulation powder and filler powder

    CN114655938A

  • High thermal conductivity filler

    JP2011184507A

  • Aluminum nitride sintered granule

    JP2022147702A